Original Articles Preoperative Hematological Parameters for Predicting Ovarian Torsion in Patients with Mature Cystic Teratoma - Lee J; Park J; Lee HJ; Kim MJ; Lee YH; Chong GO; Hong DG; Lee TH (Dove Medical Press, 2021)
Jisun Lee,1 Jinyoung Park,2 Hyun Jung Lee,1 Mi Ju Kim,1 Yoon Hee Lee,3 Gun Oh Chong,3 Dae Gy Hong,3 Taek Hoo Lee1 1Department of Obstetrics and Gynecology, School of Medicine, Kyungpook National University, Kyungpook National University Hospital, Daegu, Republic of Korea; 2Department of Surgery, School of Medicine, Kyungpook National University, Kyungpook National University Hospital, Daegu, Republic of Korea; 3Department of Obstetrics and Gynecology, School of Medicine, Kyungpook National University, Kyungpook National University Chilgok Hospital, Daegu, Republic of KoreaCorrespondence: Taek Hoo LeeDepartment of Obstetrics & Gynecology, 130 Dongdeok-ro, Jung-gu, Daegu, 41944, Republic of KoreaTel +82-53-200-5735Fax +82-53-423-7905Email thlee@knu.ac.krObjective: The objective of this study is to evaluate the preoperative hematological parameters to predict ovarian torsion in patients with ovarian mature cystic teratoma. We also analyzed the diagnostic value of these makers to predict ovarian necrosis in cases of torsion as well as the effect of torsion on ovarian reserve.Patients and Methods: This is a retrospective study of 132 patients who received either laparoscopic or laparotomy surgery for OMCT at a single university hospital. Clinical characteristics and preoperative hematological parameters were compared between patients with or without torsion. Patients with torsion were further classified as infarction and non-infarction group. Preoperative parameters were compared between the two groups as well.Results: White blood cell (WBC) count, neutrophil percent, neutrophil count, and neutrophil to lymphocyte ratio (NLR) were higher in the torsion group (n=37) than the non-torsion group (n=95) (p< 0.05 for all). Although statistically insignificant, the preoperative anti-Mullerian hormone (AMH) was lower in the torsion group than the non-torsion group (4.07 ± 3.38 vs 6.1 ± 3.6, p=0.122). In cases of torsion, the infarction group showed higher WBC count and lymphocyte count but lower hemoglobin level and platelet to lymphocyte ratio (PLR) than the non-infarction group (p< 0.05 for all).Conclusion: The WBC count, neutrophil percent, neutrophil count, and NLR were higher in the cases of OMCT with torsion, and these parameters may be useful to diagnose OMCT with torsion. Also, adnexal torsion may deteriorate ovarian reserved as indicated by decreased AMH in torsion group.Keywords: leukocyte counts, necrosis, ovarian neoplasm, ovarian teratoma, ovarian reserve, torsion